Asuhan Keperawatan Jiwa Pada Tn.S Dengan Masalah Utama Gangguan Persepsi Sensori: Halusinasi Pendengaran Akibat Skizofrenia Takterinci Di Ruang Srikandi Rsjd dr. Amino Gondohutomo Provinsi Jawa Tengah - Iin Nur Aeni; Titi Sri Suyanti; Tati Karyawati (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Schizophrenia is a group of psychotic reactions that affect various areas of an individual's functioning, including thinking, communicating, feeling and expressing emotions, as well as a brain disorder characterized by disorganized thoughts, delusions, hallucinations and strange behavior. Data from the World Health Organization (WHO) in 2019 shows that 1 in every 8 people or 970 million people throughout the world live with mental disorders such as anxiety disorders, depression, schizophrenia, bipolar disorder, 24 million people worldwide suffer from severe mental disorders such as schizophrenia. or 1 in 300 people (0.32%) this figure is 1 in 222 people (0.45%) among adults, and 280 million people suffer from depression including 23 million children and adolescents, 40 million people suffer from bipolar disorder, 301 million people experience anxiety disorders, including 58 million children and adolescents (WHO, 2022).